ANALYSIS ON WHEEL-RAIL MATCHING CHARASTERISTICS OF HIGH-SPEED RAILWAY - YI MeiLing (Jixie qiangdu, 2022)
To improve the wheel-rail relationship of high-speed EMUs due to the deterioration of wheel treads central hollow wear, wheel-rail matching characteristics of various treads were analyzed. Due to the loss of gravity stiffness restoring force, the wheel/rail creep increases and the bad contact becomes more and more severe. The matching relations of LMA, S1002 G, XP55 and typical hollow-worn profile were compared. It was found that the selection of profile should reasonably match the suspension characteristics of bogies. The larger contact spot area of LMA and the rail contact point close to the rail top is easier to form the conformal contact, which is not conducive to the delay of hollow-worn. The equivalent conicity of S1002 G and the position of the contact points change nonlinearly in the narrower scope, which is harmful to uniform wear; the peak of the contact spot area at the nominal rolling circle position of the wheel tread is easy to form the concentrated abrasion. XP55 maintains a（near） linear change in the equivalent conicity and contact spot area, and the initial rail contact position close to the rail gauge corner of 7 mm is benefit to overcome the conformal contact on the rail top. XP55 can be used for reference to optimize high-speed wheel-rail matching relationship.